Can protection motivation theory predict protective behavior against ticks? - Mette Frimodt Hansen; Pelle Korsbaek Sørensen; Anja Elaine Sørensen; Karen Angeliki Krogfelt (BMC, 2023)
Abstract Background Cases of reported tick-borne diseases in humans have increased over the past decades. Strategies informing the public about ticks, their associated diseases, and preventive measures are often highlighted as important in limiting pathogen transfer and disease. However, knowledge about the motivation for people to apply preventative measures is sparse. Methods The aim was to examine if Protection Motivation Theory, a model of disease prevention and health promotion, can predict the use of protective measures against ticks. Ordinal logistic regression and Chi-square tests were used on data from a cross-sectional survey with respondents from Denmark, Norway, and Sweden (n = 2658). We examined the effect of (1) the perceived seriousness of tick bites, Lyme borreliosis (LB), and tick-borne encephalitis (TBE), and (2) the perceived probability of getting a tick bite, Lyme borreliosis, and tick-borne encephalitis on protection against ticks. Finally, we examined if there was an association between the use of a protective measure and the perceived efficacy of that measure. Results The perceived seriousness of a tick bite and LB significantly predict who is more likely to apply protective measures for all three countries combined. The perceived seriousness of TBE did not significantly predict the level of adoption of protective measures applied by respondents. The perceived likelihood of getting a tick bite within the next 12 months and the perceived likelihood of getting LB if bitten by a tick significantly predicted the application of protective measures. However, the increases in the likelihood of protection were very small. The application of a certain type of protection was always correlated with the perceived efficacy of the same protective measure. Conclusion Some variables of PMT may be used to predict the level of adoption of protection applied against ticks and tick-borne diseases. We found that the perceived seriousness of a tick bite and LB significantly predict the level of adoption protection. The perceived likelihood of getting a tick bite or LB also significantly predicted the level of adoption of protection, although the change was very small. The results regarding TBE were less clear. Lastly, there was an association between applying a protective measure and the perceived efficacy of the same measure.